The Value of Blood Urea Nitrogen in the Prediction of Risks of Cardiovascular Disease in an Older Population - Lan, Qin; Zheng, Liang; Zhou, Xiaohui; Wu, Hong; Buys, Nicholas; Liu, Zhongmin; Sun, Jing; Fan, Huimin (Frontiers in Cardiovascular Medicine, 2021)
Background: High blood urea nitrogen (BUN) is associated with adverse outcomes in patients with cardiac disease risks. However, no study has explored whether BUN can predict the risk of cardiovascular disease (CVD) in the healthy older population. This study aims to explore the incidence and risk factors of CVD among a healthy older population community in China. Design and Methods: This study was designed as a cohort study with a 4-year follow-up. We recruited 5,000 older people among 137,625 residents of the Gaohang community. In the baseline, subjects were asked to participate in medical screening and biological tests, and answered survey questions. During the follow-up period (2014–2017), the researchers regularly tested the subjects' indicators and assessment scales. We monitored the occurrence of CVD and explored the relationship between BUN and CVD via a Cox regression analysis. Results: During the follow-up, subjects were newly diagnosed with CVD including heart failure (HF), heart disease events, atrial fibrillation, diabetes, hypertension, metabolic syndrome, and kidney disease. The Cox regression analysis found an association between baseline BUN and incident CVD in female subjects, with higher BUN associated with increased risk of AF in females and kidney disease in both male and females. No association was found between BUN and CVD in male subjects. Conclusions: Current results indicate that BUN is a valuable predictive biomarker of CVD. A higher BUN level (>13.51 mg/dL) is associated with an increased occurrence of HF but a decreased occurrence of diabetes and metabolic symptoms in normal older females.